2022
DOI: 10.3390/jmse10020139
|View full text |Cite
|
Sign up to set email alerts
|

Review of Ship Behavior Characteristics in Mixed Waterborne Traffic

Abstract: Through the continuous development of intellectualization, considering the lifecycle of ships, the future of a waterborne traffic system is bound to be a mixed scenario where intelligent ships of different autonomy levels co-exist, i.e., mixed waterborne traffic. According to the three modules of ships’ perception, decision-making, and execution, the roles of humans and machines under different autonomy levels are analyzed. This paper analyzes and summarizes the intelligent algorithms related to the three modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…This Special Issue, "Data-/Knowledge-Driven Behavior Analysis of Maritime Autonomous Surface Ships", includes twelve contributions [1][2][3][4][5][6][7][8][9][10][11][12] published during 2021-2022. Maritime traffic data (e.g., radar data, AIS data, and CCTV data) provide designers, officers on watch, and traffic operators with extensive information about the states of ships at present and in history, representing a treasure trove for behavior analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue, "Data-/Knowledge-Driven Behavior Analysis of Maritime Autonomous Surface Ships", includes twelve contributions [1][2][3][4][5][6][7][8][9][10][11][12] published during 2021-2022. Maritime traffic data (e.g., radar data, AIS data, and CCTV data) provide designers, officers on watch, and traffic operators with extensive information about the states of ships at present and in history, representing a treasure trove for behavior analysis.…”
mentioning
confidence: 99%
“…Tang et al [7] analyzed and summarized the intelligent algorithms for MASS related to risk perception, decision making, and execution that have been published in the last five years. By reviewing the existing achievements, the authors concluded that the establishment of a risk perception system with digital and visual integration would improve the quality of risk identification.…”
mentioning
confidence: 99%